Multidrug resistance in urinary E. coli higher in males compared to females - Narayan Khanal; Colin H. Cortie; Chloe Story; Sandra Jones; Kylie J. Mansfield; Spiros Miyakis; Caitlin Keighley (BMC Urology)
Abstract Background Urinary tract infections (UTIs) are common however the widespread use of antibiotics has led to a rise in antimicrobial resistance (AMR) amongst uropathogens, rendering a significant proportion of infections resistant to first line treatment. AMR in UTIs may differentially affect men and women, younger and older patients. The purpose of this study was to investigate MDR (multi-drug resistance) and AMR in males and females in an Australian health district. Methods There were 85,844 E. coli urinary isolates (2007–2020) analysed from adult patients. An E. coli isolate with MDR was defined as resistant to at least 1 agent in ≥ 3 antimicrobial classes. Chi-square tests and relative risk were calculated by comparing resistance in males and females and by age for antibiotics commonly used to treat UTIs in hospital and community collected samples. Results There was a higher proportion of MDR E. coli in males compared to females in both the community (6.4% vs. 5.2%, P < 0.001) and hospital datasets (16.5% vs. 12.8%, P < 0.001). The proportions of MDR for both males and females were significantly higher in the hospital setting. Resistance rates were higher in males compared to females for amoxicillin, amoxicillin/clavulanate, cephalexin and norfloxacin (p < 0.005), though not for trimethoprim. Antibiotic resistance was seen to increase over time. Conclusions A higher proportion of MDR E. coli were noted in urine samples from males compared with females, possibly due to the increased likelihood of prior treatment for UTIs in men. Antimicrobial stewardship interventions could be targeted towards this cohort to address increasing rates of AMR.